The anti‐parasitic drug miltefosine suppresses activation of human eosinophils and ameliorates allergic inflammation in mice. (2nd February 2021) - Knuplez, Eva; Kienzl, Melanie; Trakaki, Athina; Schicho, Rudolf; Heinemann, Akos; Sturm, Eva M.; Marsche, Gunther
Abstract : Background and Purpose: Miltefosine is an alkylphosphocholine drug with proven effectiveness against various types of parasites and cancer cells. Miltefosine is not only able to induce direct parasite killing but also modulates host immunity, for example by reducing the severity of allergies in patients. To date, there are no reports on the effect of miltefosine on eosinophils, central effector cells involved in allergic inflammation. Experimental Approach: We tested the effect of miltefosine on the activation of human eosinophils and their effector responses in vitro and in mouse models of eosinophilic migration and ovalbumin‐induced allergic lung inflammation. Key Results: The addition of miltefosine suppressed several eosinophilic effector reactions such as CD11b up‐regulation, degranulation, chemotaxis and downstream signalling. Miltefosine significantly reduced the infiltration of immune cells into the respiratory tract of mice in an allergic cell recruitment model. Finally, in a model of allergic inflammation, treatment with miltefosine resulted in an improvement of lung function parameters. Conclusion and Implications: Our observations suggest a strong modulatory activity of miltefosine in the regulation of eosinophilic inflammation in vitro and in vivo . Our data underline the potential efficacy of miltefosine in the treatment of allergic diseases and other eosinophil‐associated disorders and may raise important questions regarding the immunomodulatory effect of miltefosine in patients treated for leishmania infections.